The Potential to Reduce Pollutant Emissions from Individual Household Sector by Involving Citizens as Project Stockholders - Pietras-Szewczyk, Małgorzata (European Journal of Sustainable Development, 2021)
Atmospheric pollutants come from many sources, mainly from industry and transport as well as from households. Each sector is characterized by different specificity that concerns both the volume of emissions and the type of pollutants emitted. Each of them has also different potential to reduce the load of emissions. The purpose of this article is to show the role and potential of individual households in the fight to improve air quality. The article also aims at showing that by raising public awareness and changing habits of individual users of central heating installations, it is possible to reduce the amount of pollutants emitted from this sector. An important part of the work is a summary of a survey conducted among 150 residents of Wroclaw. The study entitled Awareness of residents of the city of Wroclaw about the sources of atmospheric pollution contained 27 questions regarding general knowledge and air quality in Wroclaw.